2017
DOI: 10.1021/acs.biochem.7b00681
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of DNA Supercoil Geometry byMycobacterium tuberculosisGyrase

Abstract: Mycobacterium tuberculosis encodes only a single type II topoisomerase, gyrase. As a result, this enzyme likely carries out the cellular functions normally performed by canonical gyrase and topoisomerase IV, both in front of and behind the replication fork. In addition, it is the sole target for quinolone antibacterials in this species. Because quinolone-induced DNA strand breaks generated on positively supercoiled DNA ahead of replication forks and transcription complexes are most likely to result in permanen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 58 publications
3
28
0
Order By: Relevance
“…Furthermore, the presence of this C-loop indirectly slightly modulates the DNAstimulated ATPase activity of Mtb DNA gyrase and has little impact on DNA-strand passage. This modulation could in part explain why the N-gate region is essential for the recognition of DNA geometry by Mtb gyrase, as was highlighted recently (Ashley et al, 2017). Therefore, our observations strengthen the idea that Mtb DNA gyrase must escape from the ''extremely open'' N-gate conformation before it can proceed onto the productive catalytic pathway.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, the presence of this C-loop indirectly slightly modulates the DNAstimulated ATPase activity of Mtb DNA gyrase and has little impact on DNA-strand passage. This modulation could in part explain why the N-gate region is essential for the recognition of DNA geometry by Mtb gyrase, as was highlighted recently (Ashley et al, 2017). Therefore, our observations strengthen the idea that Mtb DNA gyrase must escape from the ''extremely open'' N-gate conformation before it can proceed onto the productive catalytic pathway.…”
Section: Discussionsupporting
confidence: 85%
“…This ~20-fold time difference between the two reactions likely reflects the acute temporal requirement to rapidly remove positive supercoils that accumulate in front of the replication fork as compared to the maintenance of steady state levels of negative DNA supercoiling. 6364…”
Section: Resultsmentioning
confidence: 99%
“…4447 A recent study by Ashley et al demonstrated that M. tuberculosis gyrase maintains 2-3-fold lower levels of cleavage complexes on positively compared to negatively supercoiled DNA in the absence or presence of fluoroquinolones. 48 This attribute makes gyrase a safer enzyme (for cells) to work ahead of DNA tracking systems, but may also affect the cytotoxicity of fluoroquinolones.…”
Section: Resultsmentioning
confidence: 99%